South African Buffalo-Derived Theileria parva Is Distinct From Other Buffalo and Cattle-Derived T. parva - Maboko, Boitumelo B.; Sibeko-Matjila, Kgomotso P.; Pierneef, Rian; Chan, Wai Y.; Josemans, Antoinette; Marumo, Ratselane D.; Mbizeni, Sikhumbuzo; Latif, Abdalla A.; Mans, Ben J. (Frontiers in Genetics, 2021)
Theileria parva is a protozoan parasite transmitted by the brown-eared ticks, Rhipicephalus appendiculatus and Rhipicephalus zambeziensis. Buffaloes are the parasite’s ancestral host, with cattle being the most recent host. The parasite has two transmission modes namely, cattle-cattle and buffalo-cattle transmissions. Cattle-cattle T. parva transmission causes East Coast fever (ECF) and January disease syndromes. Buffalo to cattle transmission causes Corridor disease. Knowledge on the genetic diversity of South African T. parva population will assist in determining its origin, evolution and identify any cattle-cattle transmitted strains. To achieve this, genomic DNA of blood and in vitro culture material infected with South African isolates (8160, 8301, 8200, 9620, 9656, 9679, Johnston, KNP2, HL3, KNP102, 9574 and 9581) were extracted and paired-end whole genome sequencing using Illumina HiSeq 2500 was performed. East and southern African sample data (Chitongo Z2, Katete B2, Kiambu Z464/C12, Mandali Z22H10, Entebbe, Nyakizu, Katumba, Buffalo LAWR and Buffalo Z5E5) was also added for comparative purposes. Data was analyzed using BWA and SAMtools variant calling with the T. parva Muguga genome sequence used as a reference. Buffalo-derived strains had higher genetic diversity, with twice the number of variants compared to cattle-derived strains, confirming that buffaloes are ancestral reservoir hosts of T. parva. Host specific SNPs however, could not be identified among the selected 74 gene sequences. Phylogenetically, strains tended to cluster by host with South African buffalo-derived strains clustering with buffalo-derived strains. Among the buffalo-derived strains, South African strains were genetically divergent from other buffalo-derived strains indicating possible geographic sub-structuring. Geographic sub- structuring was also observed within South Africa strains. The knowledge generated from this study indicates that to date, ECF is not circulating in buffalo from South Africa. It also shows that T. parva has historically been present in buffalo from South Africa before the introduction of ECF and was not introduced into buffalo during the ECF epidemic.